2019
DOI: 10.1016/j.jaci.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

NAVIGATE II: Randomized, double-blind trial of the exhalation delivery system with fluticasone for nasal polyposis

Abstract: EDS-FLU produces clinically and statistically significant improvement in all 4 diagnostically defining disease symptoms, polyp grade, and quality of life in patients with chronic rhinosinusitis with NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 51 publications
7
109
0
1
Order By: Relevance
“…Forty percent and 30% of enrolled patients were converted to nonsurgical candidates at the week 12 and end‐of‐study visit, respectively, based on a decrease in SNOT 22 score below the threshold of 20. Because nasal congestion is the most prevalent and severe individual symptom of the SNOT‐22, a minimum nasal congestion score of 2 was required to be in line with other clinical studies in the field . Patients from our study reported a baseline average nasal congestion score of 3.8, in line with that of presurgical patients reported by Abdalla et al .…”
Section: Discussionsupporting
confidence: 68%
“…Forty percent and 30% of enrolled patients were converted to nonsurgical candidates at the week 12 and end‐of‐study visit, respectively, based on a decrease in SNOT 22 score below the threshold of 20. Because nasal congestion is the most prevalent and severe individual symptom of the SNOT‐22, a minimum nasal congestion score of 2 was required to be in line with other clinical studies in the field . Patients from our study reported a baseline average nasal congestion score of 3.8, in line with that of presurgical patients reported by Abdalla et al .…”
Section: Discussionsupporting
confidence: 68%
“…EDS‐FLU is a new treatment with potential to improve medical care of CRS in patients who do not respond satisfactorily to conventional nasal steroids by enabling reliable and consistent outpatient delivery of steroid to high and deep target sites of inflammation . In addition, studies have suggested the possibility that direct EDS device benefits could be produced by the effects of carbon dioxide in exhaled breath (influencing inflammatory mediator and neuropeptide activity), by removal of nitric oxide, by positive pressure, or by change in pH .…”
Section: Discussionmentioning
confidence: 99%
“…Two large, randomized controlled trials were performed to establish the efficacy of EDS‐FLU in patients with CRSwNP . However, practical data that more closely resemble “real‐world evidence” for the benefits of long‐term treatment are also valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of the articles were excluded as they focused on fluticasone use in lower airway disease (n = 129), were centered on exhaled gas measurements for the evaluation and monitoring of lower airway disease (n = 67), or discussed use of the EDS in migraine therapy (n = 4). The majority of the evidence surrounding the efficacy of EDS‐FLU is from 4 large‐scale studies that were performed as part of the FDA‐approval process, namely EXHANCE‐3, EXHANCE‐12, NAVIGATE I, and NAVIGATE II . The relevant data and outcomes these trials are summarized in what follows (Table ).…”
Section: Resultsmentioning
confidence: 99%